Psychological and Pedagogical Conditions for the Development of Professionally Important Qualities of Future Teachers of Preschool Educational Institutions in Training - Tsybulyak, Natalya Yurevna (Psychological Prospects Journal, 2012)
The views of scientists on the psychological and pedagogical conditions for the development of professionally important qualities during training were considered in the article. The conditions promoting these qualities in the future educators of preschool educational institutions were defined.